2006
DOI: 10.1038/nature05080
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the dynamics of RNA degradation by ribonuclease II and its RNA-bound complex

Abstract: RNA degradation is a determining factor in the control of gene expression. The maturation, turnover and quality control of RNA is performed by many different classes of ribonucleases. Ribonuclease II (RNase II) is a major exoribonuclease that intervenes in all of these fundamental processes; it can act independently or as a component of the exosome, an essential RNA-degrading multiprotein complex. RNase II-like enzymes are found in all three kingdoms of life, but there are no structural data for any of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
298
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(315 citation statements)
references
References 29 publications
17
298
0
Order By: Relevance
“…98 RNase II and RNase R belong to the RNR family. Based on sequence analysis and comparison with the RNase II structure, [99][100][101] RNase R consists of a central nuclease domain, two cold-shock (CSD) domains near the N-terminal region of the protein, an S1 domain and a highly basic C-terminal region. 102 While not detected in our complementation screen of csdA deletion strain (above) overproduction of RNase R or CspA complemented the cold-sensitive phenotype of the deletion strain.…”
Section: Cold-inducible Exoribonucleasesmentioning
confidence: 99%
“…98 RNase II and RNase R belong to the RNR family. Based on sequence analysis and comparison with the RNase II structure, [99][100][101] RNase R consists of a central nuclease domain, two cold-shock (CSD) domains near the N-terminal region of the protein, an S1 domain and a highly basic C-terminal region. 102 While not detected in our complementation screen of csdA deletion strain (above) overproduction of RNase R or CspA complemented the cold-sensitive phenotype of the deletion strain.…”
Section: Cold-inducible Exoribonucleasesmentioning
confidence: 99%
“…The catalytic activity is provided by a 10th essential subunit, Rrp44p (2,5,6). This protein is similar to RNase II in that it contains three putative RNA binding domains that flank an RNB domain (3,(7)(8)(9)(10). The RNB domain is responsible for the 3′ exonuclease activity of the exosome (3).…”
Section: Dis3 | Saccharomyces Cerevisiaementioning
confidence: 99%
“…rrp44 contains an N terminal endonuclease domain-which seems to be relatively static-and a more flexible carboxy terminal part that resem bles bacterial rNase ii, as both contain three rNa binding domains-cSD1, cSD2 and S1-and a catalytic domain. three previous crystal structures of rNase ii and rrp44 (Frazao et al, 2006;Lorentzen et al, 2008;Bonneau et al, 2009) had different orien tations of cSD1 and cSD2 relative to the rest of the protein. Malet et al (2010) found that cSD1 is slightly shifted compared with previous structures and that cSD2 does not display well ordered density in the absence of rNa, but becomes more ordered in its presence (Malet et al, 2010).…”
Section: Flexibility Within the Exosomementioning
confidence: 83%